Computational chemistry experiments performed directly on a blockchain virtual computer. Issue 18 (27th April 2020) - Hanson-Heine, Magnus W. D.; Ashmore, Alexander P.
Abstract : Blockchain technology has had a substantial impact across multiple disciplines. This study proves that physical simulations can be performed entirely within a blockchain virtual machine. These simulations have improved reproducibility, provenance, and less potential for censorship. Abstract : Blockchain technology has had a substantial impact across multiple disciplines, creating new methods for storing and processing data with improved transparency, immutability, and reproducibility. These developments come at a time when the reproducibility of many scientific findings has been called into question, including computational studies. Here we present a computational chemistry simulation run directly on a blockchain virtual machine, using a harmonic potential to model the vibration of carbon monoxide. The results demonstrate for the first time that computational science calculations are feasible entirely within a blockchain environment and that they can be used to increase transparency and accessibility across the computational sciences.